2008
DOI: 10.1002/ar.20836
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Diabetes‐Induced Palate Defects by Maternal Immune Stimulation

Abstract: Maternal diabetes can induce a number of developmental abnormalities in both laboratory animals and humans, including deformities of the face and palate. The incidence of birth defects in newborns of women with diabetes is approximately 3 to 5 times higher than among nondiabetics. In mice, nonspecific activation of the maternal immune system can reduce fetal abnormalities caused by various etiologies including hyperglycemia. This study was conducted to determine whether nonspecific maternal immune stimulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Hypertensive disorders and antihypertensive medications use in early pregnancy have both been suggested to affect fetal development through teratogenic mechanisms (van Gelder et al, 2010). Other conditions, including diabetes (Spilson et al, 2001;Hrubec et al, 2009;Stott-Miller et al, 2010), seizures (Gadoth et al, 1987;Friis, 1989), and colds (Lin et al, 2014) have also been linked to oral clefts. Whether such conditions directly or indirectly affect palatogenesis by use of medications is possible (Hviid and Molgaard-Nielsen, 2011) but unclear to date.…”
Section: Seizures Nomentioning
confidence: 99%
See 1 more Smart Citation
“…Hypertensive disorders and antihypertensive medications use in early pregnancy have both been suggested to affect fetal development through teratogenic mechanisms (van Gelder et al, 2010). Other conditions, including diabetes (Spilson et al, 2001;Hrubec et al, 2009;Stott-Miller et al, 2010), seizures (Gadoth et al, 1987;Friis, 1989), and colds (Lin et al, 2014) have also been linked to oral clefts. Whether such conditions directly or indirectly affect palatogenesis by use of medications is possible (Hviid and Molgaard-Nielsen, 2011) but unclear to date.…”
Section: Seizures Nomentioning
confidence: 99%
“…Other possible maternal risk factors include medication use, infections and specific health conditions (Mossey et al, 2009). In particular, diabetes (Spilson et al, 2001;Hrubec et al, 2009;Stott-Miller et al, 2010), hypertension (Hurst et al, 1995), and seizures (Gadoth et al, 1987;Friis, 1989) have been implicated as potential risk factors. Although many studies of environmental factors have been based on small sample sizes, it is unlikely that one single exposure will explain most of the risk associated with clefts, but rather that diverse exposures occurring at critical times in development will be independent contributing risk factors and together result in clefting.…”
Section: Introductionmentioning
confidence: 99%
“…Torchinsky and colleagues () found that nonspecific immunostimulation with injected rat splenocytes 3 weeks before mating led to a fourfold reduction in the incidence of malformed fetuses in a streptozocin‐induced diabetic mouse models. Subsequent studies have demonstrated similar reductions in NTDs and associated congenital malformations using other immune activators including: granulocyte‐macrophage colony‐stimulating factor (GM‐CSF), and interferon‐γ (IFNγ) (Hrubec et al, ), which are pleiotropic cytokines known for their roles in inflammation and immune cell regulation (Young and Hardy, ; Hamilton and Anderson, ).…”
Section: Introductionmentioning
confidence: 99%
“…Using streptozotocin (STZ), a diabetogenic agent, to induce craniofacial defects in mice, Hrubec et al 15,16 reported significantly reduced maxillary and mandibular shortening in fetuses from hyperglycemic dams that also received GM-CSF or interferon-gamma (IFN-g) by IP injection. Maternal diabetes also increases cardiovascular defects in humans and rodents.…”
Section: Immune Protection During Development 133mentioning
confidence: 99%